EFFECTIVENESS OF THE BACTH I TEACHING CAMPUS PROGRAM AGAINST EXISTENCE OF PARTNER SCHOOLS DURING THE COVID-19 PANDEMIC - Mavianti Mavianti (Proceeding International Seminar of Islamic Studies, 2022)
The covid-19 pandemic has an impact on all fields, not least the field of education. This condition requires to the learning process that usually done face to face must switch online. This change certainly provides its own challenges and problems for school, especially those in the 3T area and have C accreditation. The presence of batch I teaching campus program rolled out by the government through the Ministry of Education and Culture aims to involve students as a part of strengthening literacy and numeracy while helping learning in partner schools. The participation and active role students in the school has new impact and hope so that the school continues to improve itself for the realization of the vision and mission of the school. Even the school gets a positive response and trust from the surrounding community by sending their children to the school. The school is also increasingly excited in developing and advancing education for the creation of a quality generation.Keyword: Teaching Campus Program, Existence, Partner School